Who will be the early adopters of automated vehicles? Insights from a survey of electric vehicle owners in the United States. (June 2019) - Hardman, Scott; Berliner, Rosaria; Tal, Gil
Highlights: We survey plug in electric vehicle (PEV) buyer preferences for automated vehicles. The study finds 5 clusters based on interest in automated vehicles. Pioneers are the most likely to purchase automated vehicles. These consumers have good knowledge and positive perceptions of the vehicles. They also have high incomes and positive attitudes towards new technologies. Abstract: Most major automakers are developing vehicles with some level of automated driving capability. These vehicles range from those with adaptive cruise control to full driverless vehicles. These vehicles are collectively referred to as automated vehicles. The adoption of automated vehicles by consumers is not well understood. It is likely that the first buyers will be typical early adopters i.e. consumers who have different lifestyles, attitudes, and socio-demographic profiles compared to the general population. Using a questionnaire survey of 2715 consumers in 36 states in the USA, we investigate the attitudes of early adopters of one automotive technology: plug-in electric vehicles (PEVs). This sample was selected so that the perceptions and purchase intentions of early adopters could be investigated. This is opposed to assessing the attitudes of the public who are unlikely to be knowledgeable about automated vehicles and unable to accurately assess the vehicles and estimate their own purchase intentions. This study finds that PEV early adopters have positive perceptions of automated vehicles. However, being a PEV adopter does not necessarily lead to interest in purchasing an automated vehicle. PEV adopters are clustered into 5 different groups with differing levels of interest in automated vehicles (from "Pioneers" to "Laggards"). The results suggest that automated vehicles are likely to be purchased by a small group of pioneering consumers. These "Pioneers" are likely to be high income consumers, with good knowledge and positive perceptions of the automated vehicles (on safety, comfort, and purchase price), and positive attitudes towards technology in general.